Intention, Motivations, and Barriers to Emigration of Nursing Students in Colombia - Peña Alfaro, Bairon Steve; Torres Díaz, Nancy Viviana (Investigación y Educación en Enfermería, 2024)
Objective. To explore the intention, motivations, and barriers to emigrate of final semester nursing students from Colombia. Methods. Quantitative, descriptive, and cross-sectional study with participation by 556 last-semester students matriculated in 26 undergraduate nursing programs in Colombia. Data were collected through an online questionnaire. Results. The study found that 84% of the participants consider among their plans as future nursing professionals to emigrate to practice their profession in another country. Destinations of preference for those who have thought of emigrating include countries, like Canada (63.5%), Spain (57.7%), Germany (44.9%), and the United States (44.4%). The main reasons that motivate nursing students to emigrate when they complete their professional studies are: better remuneration (81.6%), better quality of life (67.9%), greater professional growth (64.1%), greater job stability (54.7%), and more employment options (49.8%). In turn, the reasons that discourage nursing students from emigrating when they complete their professional studies are: language (71.9%), going away from the family (60.6%), and the complexity of the emigration process (55.4%). Conclusion. The findings of this research show that a notable proportion of last-semester nursing students consider among their plans to emigrate to practice in another country when they receive their degree. Knowing the intentions, motivations, and barriers to emigrate of future nurses will permit having elements to design strategies that improve the retention of professionals in Colombia.